The Juridical Implications of the Transfer of Inheritance without the Consent of All Heirs - Prasasti, Windra Anggi (Jurnal Konstatering, 2022)
This study aims to analyze: 1). The juridical implications of the transfer of inheritance without the approval of all heirs 2). Legal protection for heirs against the transfer of inheritance without the consent of all heirs. The approach method in this research is a sociological juridical approach. The research specifications used are descriptive analytical research. This type of data uses primary data and secondary data. Collecting data by interview method and literature study. The data analysis method used is qualitative analysis. The results of the study concluded: 1) The juridical implication of the transfer of inheritance without the approval of all heirs is an act against the law as stipulated in Article 1365 of the Civil Code, so that the sale-purchase agreement is of course detrimental to the legal heirs which results in the reduction of the object of inheritance. Legal certainty regarding the sale and purchase of inherited land without the consent of the heirs is guaranteed by the Legislation in Article 1471 of the Civil Code, which states that buying and selling other people's goods is void, and can provide a basis for reimbursement of costs, losses and interests. 2) Legal protection for heirs against the transfer of inheritance without the approval of all heirs Legal protection for heirs against the transfer of inheritance without the consent of all heirs if a certificate has been issued on behalf of another party is given repressive protection, namely filing a lawsuit to the Court. In the criminal law code relating to the sale of inheritance, especially inherited land sold by heirs, it does not involve the approval of other heirs, which can be entangled with criminal sanctions. This is as explained in Article 372 of the Criminal Code regarding embezzlement and also Article 385 of the Criminal Code relating to land grabbing. In addition to criminal penalties, the injured heirs can sue in a civil manner with a lawsuit against the law.Keywords: Assets; Implications; Inheritance; Transfer.